SCREENING ANTIBACTERIAL EFFECTS OF VIETNAMESE PLANT EXTRACTS AGAINST PATHOGENS CAUSED ACUTE HEPATOPANCREATIC NECROSIS DISEASE IN SHRIMPS - Nguyen, Hai Thanh; Dang, Lua Thi; Nguyen, Hanh Thi; Ha Hoang, Hai; Ngoc Lai, Ha Thi; Nguyen, Ha Thi Thanh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objectives are aimed to investigate the antibacterial properties of five Vietnamese medicinal plants against acute hepatopancreatic necrosis disease (AHPND)-caused bacterial pathogens, to verify their potentials to apply as a new treatment therapy. Methods: Extracts from plants, such as Psidium guajava leaf, Piper betle L. leaf, Phyllanthus amarus leaf, Rhodomyrtus tomentosa seed, and Allium sativum bulb, were tested against three AHPND-caused bacteria. Agar infusion and broth dilution methods were employed to evaluate extract in vitro antibacterial effects, while experiments with cultured whiteleg shrimps were applied to access their safety when applied in vivo. High-performance liquid chromatography (HPLC) analysis was applied to identify components in the extracts. Results: P. amanus and R. tomentosa extracts exerted the strongest inhibition on tested bacteria. Other extracts, including P. betel and P. guajava, were less effective, while A. sativum showed no effects against bacteria. In safety assessment experiments, we observed that only crude extracts of R. tomentosa and A. satium were safe, while others significantly reduced their survival rates. HPLC showed that extracts of high antibacterial properties had rich phenol constituents. In addition, the phenolic profile of R. tomentosa showed the presence of piceatannol. Conclusion: Considering both of antibacterial effects and safety properties altogether, we concluded that among the five examined plant materials of this study, R. tomentosa had the highest potential to apply in AHPND treatment, as only this plant showed the high effects on pathogenic bacteria while were still safe for host aquatic shrimps.